Islamic Philanthropy-Based Green Economy Assistance to Build Post-Pandemic Resilience - Eny Latifah; Fithrotin Fithrotin; Fiqih Aisyatul Farokhah (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
The focus of the post-pandemic government is to pay attention to the process of economic revival and development that still pays attention to environmental impacts in order to be able to build self-resilience with natural phenomena experienced by many countries, including Indonesia. Efforts to build resilience using the basis of Islamic philanthropy through zakat, infaq, shadaqah and waqf instruments by paying attention to the sustainability of the green economy are one way out in order to realize economic sustainability. There needs to be assistance to the community in seeking self-defense by implementing a green economy on the basis of Islamic philanthropy including assistance to educational institutions, Islamic financial institutions, and religious socio-economic institutions through socialization of saving natural resources in the use of existing facilities at their respective institutions after pandemic